Layered double hydroxide eliminate embryotoxicity of chemotherapeutic drug through BMP-SMAD signaling pathway. (February 2020) - Wang, Zhaojie; Xu, Ziping; Jing, Guoxin; Wang, Qingxiu; Yang, Li; He, Xiaolie; Lin, Lijuan; Niu, Jintong; Yang, Linnan; Li, Kun; Liu, Zhongmin; Qian, Yechang; et al.
Abstract: Recent studies indicate that exogenous chemotherapy agents can cross the placenta barrier and cause fetal toxicity, while there exists barely alternative therapy for pregnant cancer patients. Here, we show a robust protective effect of layered double hydroxide (LDH) against etoposide (VP16) induced in vitro mouse embryonic stem cells (mESCs) toxicity and in vivo embryo developmental disorders. The nano-composite system (L-V) abrogated the original VP16 generated mitochondrial mediated mESCs toxicity totally, surprisingly maintained the pluripotency without leukemia inhibitory factor (LIF) and prevented the down-regulation of ectoderm marker expression during spontaneous embryoid bodies differentiation. Fetal growth retardation, the related placenta and skeletal structural abnormalities and long-term toxicity in the offspring were generated when pregnant mice exposed to VP16, while these detrimental effects were abolished when substituted with L-V. The different uterine drug accumulation of VP16 and L-V contributed to partly cause for the functional variation. And further transcriptome analysis confirmed developmental related BMP4-SMAD6 signaling pathway is of crucial importance. Our study revealed the devastating effects of VP16 on embryonic development and the toxicity-relieve method using nano-carrier system, which will provide important guidance for clinical application of LDH as alternative therapeutic system with minimal side effects for pregnant women diagnosed with cancer.